Perlindungan Hukum Bagi Franchisee Terhadap Pemutusan Perjanjian Yang Disebabkan Franchisor Pailit - Shobahatun Nisa (Fakultas Hukum Universitas Islam Malang, 2021)
This study departs from the problem of terminating the agreement on the franchisee caused by the bankrupt franchisor. There are three problem formulations in this writing, namely how the characteristics of the franchise, how to arrange sanctions on the franchisor who breaks the franchise agreement against the franchisee due to bankruptcy, and what form of legal protection for franchisees due to bankrupt franchisor. The method of writing in this research is normative juridical. The sources of law that the authors use are primary, secondary, and tertiary sources of law. Approach to research through a conceptual approach (conceptual approach), a statutory approach (statute approach), and a historical approach (historical approach). Then the legal material analysis technique uses a qualitative descriptive technique. A franchise must have characteristics in the form of business characteristics, proven to be profitable, have standards for services and goods and / or services offered that are made in writing, easy to teach and apply, have continuous support, and must have Intellectual Property Rights (IPR). ) that has been registered. The franchisor who breaks the franchise agreement against the franchisee as a result of bankruptcy is considered to have committed an unlawful act that harms other people so that he must compensate for the loss due to this, in accordance with what is regulated in Article 1365 of the civil code book As for the form of legal protection for franchisees due to the bankrupt franchisor, the franchisee can ask for assurance from the curator regarding the continuation of the franchise agreement and can claim compensation by acting as a concurrent creditor. Key Words: Legal protection, franchisee, termination of agreement, franchisor, bankruptcy.